PENGGUNAAN OBAT ANTIEPILEPTIK SEBAGAI PENCEGAHAN MIGREN - Karema Winifred* (Neurona Majalah Kedokteran Neuro Sains, 2009)
SOME ANTIEPILEPTIC DRUGS ARE PROPOSED FOR THE PROPHYLACTIC TREATMENT OF MIGRAINE VALPROIC ACID AND ITS SODIUM SALT DIVALPROEX HAVE BEEN SHOWN TO BE EFFECTIVE IN PREVENTING MIGRAINE IN STUDIES TOPIRAMATE HAS RECENTLY BEEN PROPOSED FOR THE TREATMENT OF UNRESPONSIVE HIGH FREQUENCY MIGRAINE TAKING INTO ACCOUNT BOTH THE GABA AND GLUTAMATERGIC MECHANISMS OF ACTION GABAPENTIN LAMOTRIGINE LEVETIRACETAM AND ZONISAMIDE HAVE ALSO BEEN PROPOSED FOR MIGRAINE PROPHYLAXIS